Elective Foley’s induction in previous one caesarean section - Desai, Aneri; Shrivastav, Ritka; Dobariya, Bhumika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: American college of obstetricians and gynecologists and the American academy of family physicians recommended that pregnant women with a single previous caesarean delivery and a low-transverse incision should be offered a trial of labour. This study was planned to measure safety and efficacy of elective Foley’s induction as a method of induction in previous one caesarean section. Methods: This was a prospective study of 150 women with previous caesarean section who were candidates for TOLAC admitted in labour room. Induction of labour via Foley’s catheter was done in group A whereas group B had a spontaneous onset of labour in previous caesarean section cases. Augmentation was done, if required. Results: There was spontaneous expulsion of Foley’s catheter in 88% out of which 65.15% patients delivered vaginally and 34.84% were delivered by caesarean section. Out of 12% where Foley’s catheter had to be removed after 12 hours manually, 88.89% were delivered by caesarean section. Conclusions: A change in Bishop score after induction with Foley’s catheter in previous caesarean section leads to higher chances of successful vaginal delivery. The likelihood of successful vaginal delivery increases with increase in FLAMM score.